Identification and Analysis of Zinc Efficiency-Associated Loci in Maize - Xu, Jianqin; Wang, Xuejie; Zhu, Huaqing; Yu, Futong (Frontiers in Plant Science, 2021)
Zinc (Zn) deficiency, a globally predominant micronutrient disorder in crops and humans, reduces crop yields and adversely impacts human health. Despite numerous studies on the physiological mechanisms underlying Zn deficiency tolerance, its genetic basis of molecular mechanism is still poorly understood. Thus, the Zn efficiency of 20 maize inbred lines was evaluated, and a quantitative trait locus (QTL) analysis was performed in the recombination inbred line population derived from the most Zn-efficient (Ye478) and Zn-inefficient inbred line (Wu312) to identify the candidate genes associated with Zn deficiency tolerance. On this basis, we analyzed the expression of ZmZIP1-ZmZIP8. Thirteen QTLs for the traits associated with Zn deficiency tolerance were detected, explaining 7.6–63.5% of the phenotypic variation. The genes responsible for Zn uptake and transport across membranes (ZmZIP3, ZmHMA3, ZmHMA4) were identified, which probably form a sophisticated network to regulate the uptake, translocation, and redistribution of Zn. Additionally, we identified the genes involved in the indole-3-acetic acid (IAA) biosynthesis (ZmIGPS) and auxin-dependent gene regulation (ZmIAA). Notably, a high upregulation of ZmZIP3 was found in the Zn-deficient root of Ye478, but not in that of Wu312. Additionally, ZmZIP4, ZmZIP5, and ZmZIP7 were up-regulated in the Zn-deficient roots of Ye478 and Wu312. Our findings provide a new insight into the genetic basis of Zn deficiency tolerance.